Adaptive optics imaging in the most common inherited retinal degenerations - Samelska, Katarzyna; Kupis, Magdalena; Zaleska-Żmijewska, Anna; Szaflik, Jacek P. (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
Adaptive optics is the imaging technique of the retina. It finds use in visualizing microscopic changes in the retinal photoreceptors and the retinal blood vessels. Introducing adaptive optics as a diagnostic tool facilitated diagnosing inherited retinal diseases, such as Stargardt disease, cone-rod dystrophy, and retinitis pigmentosa. These diseases are often inherited in a heterogenous pattern. Thus, genetic testing often fails to give a certain diagnosis. Optical coherence tomography, fundus autofluorescence, fluorescein angiography, visual field examination and electrophysiological testing are vital for diagnosing patients with inherited retinal diseases. Adaptive optics imaging complements diagnosing and monitoring conditions such as Stargardt disease and cone-rod dystrophy. In this article we sum up the main characteristics of inherited retinal diseases in adaptive optics imaging.